The Effect of Murottal and Dzikir Therapy on Anxiety Levels of Cervical Cancer Patients - Slamet Purnomo; Diyanah Syolihan Rinjani Putri; S. Dwi Sulisetyawati (Indonesian Journal of Global Health Research, 2025)
Patients diagnosed with Stage IIIb cervical cancer will undergo chemotherapy treatment. The initial course of chemotherapy for individuals with cervical cancer is associated with both physical and psychological side effects. Physical side effects include fatigue, nausea, vomiting, oral ulcers, hair loss, and disorders affecting the nervous and muscular systems, as well as psychological effects such as anxiety, feelings of helplessness, shame, and diminished self-esteem. Cervical cancer undergoing the first chemotherapy will experience impaired anxiety levels, resulting in aggressive behavior and self-isolation. The application of Murottal therapy and dhikr before undergoing the first chemotherapy has a positive effect on patients. Objective: This research aimed to assess the degree of anxiety experienced by cervical cancer patients undergoing first-line chemotherapy treatment, with the incorporation of Murottal therapy and dhikr before the chemotherapy session. Method: The study employed a quasi-experimental design utilizing a one-group pre-test and post-test approach. The sample comprised 52 cervical cancer patients participating in the first chemotherapy program, selected using a total sampling method. Exclusion criteria included patients who were on anxiety-reducing medications, those in emergency medical situations, and individuals with impaired consciousness. An evaluation of anxiety levels utilized the Hamilton Rating Scale for Anxiety (HARS). The intervention consisted of Murrotal therapy and dhikr for 22 minutes and 03 seconds before the commencement of chemotherapy. Results: The Wilcoxon Signed Rank Test results yielded a statistically significant p-value of 0.000 < 0.005, indicating a notable effect of Murrotal therapy and dhikr before chemotherapy. Conclusions: Therefore, Murrotal therapy and dhikr are effective in alleviating anxiety levels among cervical cancer patients undergoing first-line chemotherapy treatment at Dr. Moewardi Hospital.